FABRICATION OF UNILATERAL OVER DENTURE WITH COMBINATION HORIZONTAL RETENTION AND VERTICAL ATTACHMENT (LABORATORY PROCEDURES) - Wahjuni, Sri; Redjeki, Sri; Wafi, Azmi Sabilakisbatul (Journal of Vocational Health Studies, 2019)
Background: Currently, there is a lot of design attachment, and every design has a different laboratory procedure. One of them is retention combination horizontal and vertical synchronization. Purpose: to know the process of making a unilateral overdenture with combination horizontal and vertical attachment (laboratory procedure). Review: Overdenture is artificial tooth receives support and the retention of one or more teeth an abutment or receives the support of an implant. Attachment is a connector owned two or more parts. One part connected with a root, teeth, or implant while the other part connected to protesa. Unilateral over denture is artificial tooth some off who just made was on the side of the jaw just. Conclusion: The manufacture of unilateral overdenture retention combination with horizontal and vertical synchronization attachment in the laboratory has many steps.